Controlling resource access in Directed Bigraphs - Grohmann, Davide; Miculan, Marino (Electronic Communications of the EASST, 2008)
We study directed bigraph with negative ports, a bigraphical framework for representing models for distributed, concurrent and ubiquitous computing. With respect to previous versions, we add the possibility that components may govern the access to resources, like (web) servers control requests from clients. This framework encompasses many common computational aspects, such as name or channel creation, references, client/server connections, localities, etc, still allowing to derive systematically labelled transition systems whose bisimilarities are congruences. As application examples, we analyse the encodings of client/server communications through firewalls, of (compositional) Petri nets and of chemical reactions.